"A woman's place is in the Cold War": American women's organizations and international relations 1945-1965 - Laville, Helen (1998)
The aim of this thesis is to explore the activities of American women's associations in the international realm. In the years immediately following the Second World War, American women saw both an opportunity and an obligation to become active in the international sphere. With obstacles and prejudices preventing their inclusion in mainstream political and diplomatic circles, many American women channelled their interest and activities in the international realm through the medium of voluntary women's organizations. These organizations participated in a number of programmes which sought to export the American way of life, and women's place within it, to overseas markets. Whilst many of these programmes were a product of American women's authentic desire to assist women in other nations, many originated with and were directed by the US government.